If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -18 = 3 + 8x Reorder the terms: -18 + 11x = 3 + 8x Solving -18 + 11x = 3 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -18 + 11x + -8x = 3 + 8x + -8x Combine like terms: 11x + -8x = 3x -18 + 3x = 3 + 8x + -8x Combine like terms: 8x + -8x = 0 -18 + 3x = 3 + 0 -18 + 3x = 3 Add '18' to each side of the equation. -18 + 18 + 3x = 3 + 18 Combine like terms: -18 + 18 = 0 0 + 3x = 3 + 18 3x = 3 + 18 Combine like terms: 3 + 18 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| 6x+8x+10=66 | | 6-(3z-1)=6-4z | | 7x-8(0)=56 | | 6x+10=4x-8 | | r^2-15=-2r | | 9(y-6)=8(y-9) | | -1/2x^2+100x | | 7(0)-8y=56 | | 13x-12=49x+24 | | 24z-48z=.72 | | 5x-14=x-(24+4x) | | w-3/2=5/8 | | -11/2h=4 | | 4(x-4)+6=6x-2(3+x) | | x+(x-12)=58 | | -31/3b=5 | | 14x-8x+9=33 | | 14x-8+9=33 | | (1+3w)(2)= | | 9m+1/4=8/1/2m+2/3 | | 4x-5=4(x+7) | | 18x+12-14x=-24 | | x-0.25+25.00=250.00 | | 7/10m=10 | | 3k=.03+7k | | 2(5-x)=-2-5+x | | 3x=9y-6 | | 20(x+8)=4(40+5x) | | (74+82+x)/3=80 | | 5y+6x=20 | | 6x+8x+12=82 | | 3+0.1(7-x)=1.3x-(0.5x-3.7) |